Modulation of Septo-Hippocampal Neural Responses in Anesthetized and Behaving Rats by Septal AMPA Receptor Mechanisms - Ibrahim, Khairunisa Mohamad (Frontiers Media S.A., 2022)
10.3389/fncir.2021.663633